Arsitektur Kontemporer Kota Pada Penggal Jalan D. I. Panjaitan, Kampung Cina Bengkulu - Dwi Rina Utami; Djoko Wijono (RUAS, 2021)
The old town of Bengkulu has elements of urban architecture with distinctive characteristics, one of which is Chinese Town. .D. I. Panjaitan is the main street of Chinese Town which is busy with vehicles, so it acts as the main image of the area. Over time, various architecture has changed in the area, as evidenced by indications of contemporary city architecture in the form of geometric spaces (building form, solid, void, skyline) and functional spaces (functions of spaces and buildings) so it is very interesting to study. Therefore, this research aims to formulate a contemporary architectural formulation of the city on D. I. Panjaitan street by using qualitative and deductive method with geometric space and functional space approach. This research reveals that the contemporary architecture of the city at D. I. Panjaitan street tends to consist of original chinese architecture on the south side and modern architecture on the south side. The functional space consists of settlement, trade and tourism areas. The character of space tends to be related to Chinese cosmological architecture, namely the concept of Sanqing, Wuxing, Bagua or Feng Shui, Jiugongtu and Jingtianzhi. These formulation shaped due to hictorical influences, policies, location, culture and important event.